The role of european green deal for carbon emission reduction - Dinçer, Hasan; Uluer, Gülsüm Sena; Lisin, Anton (Springer Science and Business Media Deutschland GmbH, 2022)
Global warming causes drought in the world so that agricultural production will decrease. With less production level, people’s access to food will be difficult. As a result, there will be an imbalance of supply and demand and the problem of inflation will arise. Furthermore, health problems will occur as people cannot eat properly. Due to climate changes caused by global warming, there is also a decrease in water resources. The preference of fossil fuels in energy production is one of the most important reasons for this. As a result of the burning of resources such as coal and oil to produce electricity, a significant amount of carbon gas is released into the atmosphere. Therefore, countries need to increase their clean energy investments. However, the costs of these energy alternatives are very high compared to fossil fuels. This situation does not attract the attention of investors. Therefore, to use clean energy instead of fossil fuels in energy production, the level of awareness on this issue should be increased. The European Green Deal also focuses on solving this climate crisis. In this context, it is aimed to use environmental resources more consciously and efficiently. It is possible to mention certain aims of this study. First, the European Green Deal aims to produce without harming the environment and nature. On the other hand, the elimination of pollution is one of the aims of this study. In this framework, it is argued that the energy sector should be decarbonized and investments in environmentally friendly technologies should be increased.
Keywords: Carbon Emission; Energy Investments; Green Deal